2008
DOI: 10.1007/s10433-008-0094-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of home-based formal help in community-dwelling older people in Finland

Abstract: Knowledge of the determinants of use of formal home-based services among older people is of particular importance for predicting the need for and cost of care in the future. The aim of this study was to estimate the frequency of formal and informal help among community-dwelling older people and to assess the determinants of home-based formal help, with a special emphasis on the frequency of help from spouse, from children and other relatives and friends. We used nationally representative cross-sectional data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
74
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 43 publications
13
74
4
Order By: Relevance
“…Consistent with previous studies from the United Kingdom (Bywaters and Harris 1998), men receive more external paid support than do women. Unlike previous results from North America (Hong 2010), but in agreement with previous results for Finland (Blomgren et al 2008), the results suggest (P value \ 0.1) that spouses have a lower probability of receiving paid support than distant relatives in Spain. This is accounted for by the lower degree of commitment and intimacy of distant relatives in comparison to spouses (Allen et al 1999).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous studies from the United Kingdom (Bywaters and Harris 1998), men receive more external paid support than do women. Unlike previous results from North America (Hong 2010), but in agreement with previous results for Finland (Blomgren et al 2008), the results suggest (P value \ 0.1) that spouses have a lower probability of receiving paid support than distant relatives in Spain. This is accounted for by the lower degree of commitment and intimacy of distant relatives in comparison to spouses (Allen et al 1999).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast with the Blomgren et al (2008) study of formal help in Finland, no need factors were linked to paid support to informal caregivers in the models. This difference can be explained because Blomgren et al also included public, volunteer and private organisations, while this study only considered private paid work.…”
Section: Discussionmentioning
confidence: 87%
“…Similar to previous studies, we found that people who had no primary caregiver, or whose primary caregiver came from outside the household, were more likely to choose home help, while those whose primary caregiver lived in the same household were more likely to go to day care [25,26]. However, even after controlling for these variables, home help service users were found to have a lower risk of functional decline than day care service users.…”
Section: Discussionsupporting
confidence: 87%
“…Others have studied factors associated with the type of care received [23][24][25]. Knowledge of the characteristics that determine the use of care is essential to designing health policies that fit society's needs [26]. In France, the publicly financed assistance is only conceived as residual of the former assistance delivered by the families.…”
Section: Introductionmentioning
confidence: 99%